China and India Go to Africa : New Deals in the Developing World - Broadman, Harry G. (2012)
Economic activity between Africa and Asia, especially China and India, is booming like never before. If the problems and imbalances this sometimes creates are managed well, this expanding engagement could be an unprecedented opportunity for Africa's growth and for its integration into the global economy.